Redefining quality of life in renal replacement therapy: a patient centered perspective - Sandhu, Manpal K.; Goyal, Kriti; Baath, Samreen K.; Sohi, Gurmanleen Singh; Parikh, Neel; Dandass, Jaiteg Singh; Kolte, Roohi (International Journal of Research in Medical Sciences, 2025)
Renal replacement therapy (RRT), encompassing hemodialysis (HD), peritoneal dialysis (PD) and kidney transplantation is essential for managing end stage renal disease (ESRD). As survival outcomes have improved, there is increasing recognition of the need to enhance quality of life (QoL) among patients undergoing RRT. However, widely used QoL assessment tools like ED-5D, SF-36 and KDQOL-SF often fail to capture the multifaceted psychosocial, emotional and existential dimensions of patients lived experiences. To better understand these limitations, we conducted a comprehensive review of PubMed indexed articles addressing QoL in RRT patients across different modalities. Our findings reveal that current tools inadequately reflect psychological distress, social role distribution and loss of autonomy and are inconsistently responsive across patient populations. Challenges such as fatigue, depression, physical decline and economic burden vary significantly and are often overlooked in standard metric. We propose a patient centered reframing of QoL assessment that includes domains such as purpose and identity, emotional and spiritual resilience, social integration, economic participation and digital empowerment. Incorporating these domains into clinical care and research design offers a more holistic approach to RRT, improving patient satisfaction, engagement and long term outcomes. This shift towards human centered metrics is essential for advancing patient centered nephrology care.